Structure and Dominance of Secondary Forest Vegetation at the Coal Mine Plan Location, East Kalimantan, Indonesia - Andi Yusuf; Nisrina Putri Hanifah (Pro-Life, 2026)
This study documents vegetation biodiversity in the secondary forest area of the PT Alhasanie coal mining concession, East Kalimantan, Indonesia, as part of the pre-mining environmental baseline survey. Surveys were conducted in 2024 using a systematic nested plot design, "strip plot," across four vegetation strata: tree DBH ≥20 cm; pole DBH 10–19.9 cm; sapling height ≥1.5 m; DBH <10 cm; and seedling (height <1.5 m). Species composition and community structure were quantified using the Importance Value Index (IVI). A total of 32 plant species were recorded. Paraserianthes falcataria dominated the tree stratum (IVI = 149.98), Macaranga gigantea dominated both the pole (IVI = 97.59) and sapling (IVI = 115.45) strata, and Eupatorium odoratum dominated the seedling stratum (IVI = 44.57). Across all strata, the vegetation is overwhelmingly composed of pioneer, disturbance-adapted, and invasive species; Dipterocarpaceae are virtually absent from the upper strata and represented only by a single Shorea leprosula individual in the sapling layer. These findings confirm a severely disturbed young secondary forest with a clear history of shifting cultivation and land encroachment—no protected species under Indonesian Ministry of Environment and Forestry Regulation No. P.106/MENLHK/SETJEN/KUM.1/12/2018 were recorded. The survey results serve as the reference condition for environmental impact assessment and provide the ecological foundation for post-mining land rehabilitation planning.